Perlindungan Hukum terhadap Pengelolaan Big Data dalam Perspektif Undang-Undang Perlindungan Data Pribadi di Indonesia - Ayumi Kartika Sari (Judge : Jurnal Hukum, 2026)
The development of digital technology has encouraged the use of big data in various sectors, such as government, banking, health and electronic commerce. This large-scale data processing provides strategic benefits for economic development and public services, but also poses risks to privacy rights and personal data protection. This research aims to analyze legal protection for big data in the perspective of Law Number 27 of 2022 concerning Personal Data Protection (UU PDP). The research method used is normative legal research with a statutory approach and a conceptual approach. The research results show that the PDP Law regulates the principles of personal data processing, data subject rights, obligations of data controllers and processors, as well as administrative and criminal sanctions mechanisms. However, implementation challenges still arise, especially related to surveillance, cyber security, and the complexity of big data technology based on algorithms and artificial intelligence. Therefore, it is necessary to strengthen institutions, harmonize regulations, and increase literacy and data security to ensure the effectiveness of legal protection in the era of digital transformation